ROOT REGENERATION OF OLIVE (OLEA EUROPAEAL.) CUTTINGS: EFFECTS OF MEDIA INJECTIONS AND DELAYED APPLICATIONS OF AUXINS - MURAT ISFENDIYAROGLU (Journal of Animal and Plant Sciences, 2023)
The rooting ability of ‘Domat’ olive cuttings is very low. Therefore, it is necessarily propagated by grafting onto seedling rootstocks. Hence, nursery tree propagation is time consuming and costly. Thus, this work was necessitated to predict the effects of auxin injections to the rooting medium to support the exogenously applied auxin. Besides, predicting the auxin sensitive phase of rooting, when the applied auxin showed the highest efficiency on cuttings treated with hormones, in different days from the cutting insertion was also aimed. Semi-hardwood olive cuttings was used. As the rooting medium, phenol-formaldehyde foam and paper pot were used.The highest rooting percentage (76.6%) was obtained from the foam, injected with 50 mg l-1IBA. However, the highest root number (2.9) and root length (54.1 mm) were observed in foam medium, without injected with IBA. As for the delayed application of hormones, cuttings treated with 5000 mg l-1 IBA on day 5, gave the highest figures of percent rooting (83.3%) and the other rooting parameters. Application of 5000 mg l-1 IBA 5 days later than cutting insertion, would be a good approach due to the highest rooting, and root quality of the cuttings of the studied cultivar and some other table olives which have difficult-to-root cuttings as well..
Keywords: IBA; NAA; Olea europaea L.; root formation; rooting plug